The Relationship Between Parenting Style on Toilet Training Achievement in Preschool Children: Evidence from Cirebon City, Indonesia - Nurcahyati, Sri; Yusuf, Yusuf; Maretalinia, Maretalinia (Ahmar Metastasis Health Journal, 2025)
Toilet training is a key developmental milestone in preschool-aged children, influenced by physical, psychological, and social factors. Poor parenting style, poor parental knowledge, and not good cultural and environmental factors play a significant role in the success of toilet training, with educational interventions shown to improve outcomes. This study aims to examine the relationship between parenting style and the success of toilet training among preschool-aged children (2–6 years). This cross-sectional quantitative study examined the relationship between parenting style and toilet training success among 50 parents of preschool-aged children (2–6 years) at UPT Majasem Community Health Center, Cirebon City, Indonesia, with the relatively small sample size noted as a limitation to generalizability. Data were collected via a validated and reliable structured questionnaire, and ethical approval was obtained from the Research Ethics Committee of Institut Teknologi dan Kesehatan Mahardika, with informed consent and confidentiality ensured for all participants. The findings of this study showed that most parents demonstrated a good parenting style (66%), and the majority of children achieved successful toilet training (80%). A significant association was found between parenting style and toilet training success (p = 0.009, Cramer’s V = 0.36), indicating a moderate relationship, with children of parents practicing a poor parenting style showing higher success rates (100%) than those with a good parenting style (69.7%). In sum, parenting style significantly affects toilet training success in preschool children, and culturally sensitive parental education is recommended to improve training outcomes and child well-being.